The cytomegalovirus gB/MF59 vaccine candidate induces antibodies against an antigenic domain controlling cell-to-cell spread - A. C. Gomes; I. A. Baraniak; A. Lankina; Z. Moulder; P. Holenya; C. Atkinson; G. Tang; T. Mahungu; F. Kern; P. D. Griffiths; M. B. Reeves (Nature Communications, 2023)
A gB/MF59 vaccine candidate for human cytomegalovirus (HCMV) provided partial protection in organ transplant patients. Here, the authors identify antibody responses in trial participants that target virally infected cells to control cell-to-cell spread of HCMV, providing a potential mechanism for the observed protection.